Pemetaan Industri Kreatif Dalam Meningktakan Pertumbuhan Ekonomi Pada Kawasan Urban di Kota Palembang - Eni, Putri; Puji Astuti, Anggun; Furqon Alfaridzhi, Muhammad; Panorama, Maya (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study aims to analyze the mapping of potential, creative economy potential, review of the contribution of the creative industry, namely according to the value of Gross Domestic Product (GDP), based on Employment, and according to Company activities and increase economic growth in urban areas in Palembang. Based on the value of Gross Domestic Product (GDP), according to Employment, as well as based on Company activities and increasing economic growth of urban areas in Palembang. The research method used in this study means: Desk research sourced from the agency based on the value of Gross Domestic Product (GDP), based on employment, and based on activity. The company also increases the economic growth of urban areas in or related departments, namely the industrial department of Palembang City and literature on the creative industry using studies that are in accordance with the value of Gross Domestic Product (GDP), based on employment, as well as according to the Company's activities and increasing economic growth in urban areas. And a short survey to the creative industry was selected to receive primary data as an evidentiary activity supported by a structured survey tool. The mapping method used is the social mapping method.